Space use of juvenile green turtles along the North Pacific coast of Costa Rica - Fanqi Wu; Veronica Valverde-Cantillo; Chelsea Durr; Mario Espinoza; Maike Heidemeyer; Christopher G. Lowe; James R. Spotila; Frank V. Paladino (PLoS ONE, 2026)
Understanding how threatened marine species use coastal areas and the extent of connectivity across different spatial and temporal scales is important for identifying critical habitats that can enhance conservation efforts in other regions of their distribution. Researchers in 2014 reported a previously unknown foraging ground for juvenile green turtles in the Gulf of Santa Elena, Costa Rica. However, there is limited information about this area and the turtles there. In this study, we investigated residency and space-use distribution of juvenile green turtles ( Chelonia mydas ) in the Gulf of Santa Elena, north Pacific coast of Costa Rica. We used acoustic telemetry to track 15 juvenile turtles (49–83 cm curved carapace length; CCL) for 19–628 days using 11 acoustic receivers placed within 5 habitat types: muddy areas, reef patches, macroalgae, rocky reefs, and mangroves. Residency Index varied among turtles, ranging from 0.17 to 1.00 (median = 0.72). It indicated a gradient from transient to high resident patterns during the study period. Space-use distribution with the Shannon index (H) ranged from 0.92 to 1.94 (median = 1.34). Large juvenile turtles exhibited significantly higher H than smaller turtles, indicating more even use of multiple stations, while small turtles showed more concentrated space use. However, the seasonal variation in H was not significant. The significant interaction between size and season suggested that there was a seasonal space-use pattern between large and small turtles.